A Companion to the literature and culture of the American west - Witschi, Nicolas S. 1966- (Blackwell companions to literature and culture, 2011)
"Few geographical regions of the United States have been more glamorized, mythologized -- and misunderstood -- than the American west. A Companion to the Literature and Culture of the American West presents an in depth and highly detailed exploration of historic and contemporary cultural expressions rooted in America's western states. Historically and culturally, the west exhibits a richness and depth of cultural expression that is often at odds with the popular imagery. Divided into three thematic sections, the companion offers a series of illuminating essays by literary and cultural scholars to reveal the complexity of the many "wests" in our imagination and reality. The first section considers the west chiefly through a historical lens, both literary and cultural, exploring such topics as exploration and Gold Rush narratives, women's writings, the growth of suburbs, class and postcolonial perspectives, and the myriad of cultural expressions from many of the west's sub-regions and population groups. The chapters in the second section present a more genre-based approach, interpreting such topics as pictorial art, cinema, cowboy poetry, autobiography, nature writing, and detective fiction. In the final part, closer, more sustained readings of specific cases illuminate some of the west's persistent questions and issues, including those related to identity, performance, representation, and marketing. A Companion to the Literature and Culture of the American West offers a fully realized portrait of the depth and complexity of cultural expressions that continue to emerge from the American west"--Provided by publisher.